2015
DOI: 10.3139/120.110798
|View full text |Cite
|
Sign up to set email alerts
|

Newly revealed features of fracture toughness behavior of spot welded dual phase steel sheets for automotive bodies

Abstract: Fracture toughness is one of the parameters, which are used to estimate the fatigue life of resistance spot-welded (RSW) joints. A spot-welded pair is affected by the shear stress of the weld zone when it is exposed to tensile load. Repetitive loads reduce the fatigue life of the spot weld, and the material splits at the spot-welded region. This study investigates the effect of welding current, weld time and nucleus size ratios on the fracture toughness of RSW of galvanized DP450 steels having 1.0 mm thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Kaynaklı imalat yöntemlerinde öncelikle sorgulanan özellik kaynağın yapısal karakteristikleri olup, statik ve dinamik yüklemelerde mekanik ve yorulma dayanımının iyi olması beklenmektedir. Bunun yanında korozyon direnci, sızdırmazlık ve estetik özellikleri de ön plana çıkmaktadır (Doruk ve diğ., 2015 ve Sevim, 2015).…”
Section: Gġrġġunclassified
“…Kaynaklı imalat yöntemlerinde öncelikle sorgulanan özellik kaynağın yapısal karakteristikleri olup, statik ve dinamik yüklemelerde mekanik ve yorulma dayanımının iyi olması beklenmektedir. Bunun yanında korozyon direnci, sızdırmazlık ve estetik özellikleri de ön plana çıkmaktadır (Doruk ve diğ., 2015 ve Sevim, 2015).…”
Section: Gġrġġunclassified
“…Kishore et al [14] studied the influcen of spot welding current on strength and nugget diameter of Zn coated DP and interstitial free steel and reported that the strength and nugget diameter of joints increases at increased levels of welding up to the evolution of expuilsion. Sevim [15] investigated fracture toughness of galvanized DP450 steel spot joints and concluded that the fracture toughness of spot joints depends on the diameter of nugget, thickness of sheet, tensile force of rupture, hardness and ratios of nucleus size. Yaghoobi et al [16] investigated RSW of DP and IF steel and reported that the TSFL of spot joints increased at increased levels of weldig current along with increase in nugget diameter.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies in the literature reporting the weldability and post-weld strength values of DP steels and TRIP steels with welding methods such as gas metal arc welding (GMAW) [13,14], laser beam welding (LBW) [15,16] and resistance spot welding (RSW) [17,18]. There is some studies about advanced high strength steels are used at automotive industry welded by EBW [19][20][21].…”
Section: Introductionmentioning
confidence: 99%